2004
DOI: 10.1038/nature02882
|View full text |Cite|
|
Sign up to set email alerts
|

Mg isotope evidence for contemporaneous formation of chondrules and refractory inclusions

Abstract: Primitive or undifferentiated meteorites (chondrites) date back to the origin of the Solar System, and thus preserve a record of the physical and chemical processes that occurred during the earliest evolution of the accretion disk surrounding the young Sun. The oldest Solar System materials present within these meteorites are millimetre- to centimetre-sized calcium-aluminium-rich inclusions (CAIs) and ferromagnesian silicate spherules (chondrules), which probably originated by thermal processing of pre-existin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

29
217
3

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 231 publications
(249 citation statements)
references
References 27 publications
29
217
3
Order By: Relevance
“…All whole-rock chondrites measured plot within ±0.01‰ Δ 25 Mg of the 334 terrestrial fractionation line, in keeping with other studies (Bizzarro et al, 2004;335 Young and Galy, 2004;Baker et al, 2005;Teng et al, 2010 (Catanzaro et al, 1966) and further 339 "external" normalisation of samples to bracketing standards (Table 1). These 340 chondritic mass independent Mg isotope ratios, average δ 26 Mg* = 0.0029 ± 0.017‰, 341 are indistinguishable from our terrestrial values, average = 0.0044 ± 0.022‰ (Thrane 342 et al, 2008).…”
Section: Chondrite Analyses 313supporting
confidence: 87%
“…All whole-rock chondrites measured plot within ±0.01‰ Δ 25 Mg of the 334 terrestrial fractionation line, in keeping with other studies (Bizzarro et al, 2004;335 Young and Galy, 2004;Baker et al, 2005;Teng et al, 2010 (Catanzaro et al, 1966) and further 339 "external" normalisation of samples to bracketing standards (Table 1). These 340 chondritic mass independent Mg isotope ratios, average δ 26 Mg* = 0.0029 ± 0.017‰, 341 are indistinguishable from our terrestrial values, average = 0.0044 ± 0.022‰ (Thrane 342 et al, 2008).…”
Section: Chondrite Analyses 313supporting
confidence: 87%
“…Al ratios close to the canonical value, suggesting that such chondrules formed at the same time as CAIs (Bizzarro et al, 2004). Considering that these initial 26 Al/ 27 Al ratios were not obtained for Al rich phases, the initial 26 Al/ 27 Al ratios obtained for bulk chondrules by ICP MS may not record the time of the last melting event of chondrules, but represent the time of chondrule precursor (silicate dust) formation (see also Fig.…”
mentioning
confidence: 88%
“…According to such a stellar origin, shortlived radionuclides were injected homogeneously in the solar nebula, hence they may be used as chronometers. This idea is supported by the measurement of U-Pb absolute ages of Caand Al-rich inclusions (CAIs) and chondrules with a Ϸ1-million year (My) resolution (8), which yields a time interval between formation of CAIs and chondrules similar to that inferred by many 26 Al- 26 Mg measurements, although a recent study reported that chondrule formation began contemporaneously with the formation of CAIs (9). On the other hand, the same short-lived radionuclides may be produced locally by intense irradiation of nebular materials by the proto-sun (10)(11)(12).…”
mentioning
confidence: 90%